Populus × canescens root suberization in reaction to osmotic and salt stress is limited to the developing younger root tip region. Issue 5 (12th September 2022) - Grünhofer, Paul; Stöcker, Tyll; Guo, Yayu; Li, Ruili; Lin, Jinxing; Ranathunge, Kosala; Schoof, Heiko; Schreiber, Lukas
Abstract: Populus is a valuable and fast‐growing tree species commonly cultivated for economic and scientific purposes. But most of the poplar species are sensitive to drought and salt stress. Thus, we compared the physiological effects of osmotic stress (PEG8000) and salt treatment (NaCl) on poplar roots to identify potential strategies for future breeding or genetic engineering approaches. We investigated root anatomy using epifluorescence microscopy, changes in root suberin composition and amount using gas chromatography, transcriptional reprogramming using RNA sequencing, and modifications of root transport physiology using a pressure chamber. Poplar roots reacted to the imposed stress conditions, especially in the developing younger root tip region, with remarkable differences between both types of stress. Overall, the increase in suberin content was surprisingly small, but the expression of key suberin biosynthesis genes was strongly induced. Significant reductions of the radial water transport in roots were only observed for the osmotic and not the hydrostatic hydraulic conductivity. Our data indicate that the genetic enhancement of root suberization processes in poplar might be a promising target to convey increased tolerance, especially against toxic sodium chloride.